Pengujian Kualitas Sistem Manage Content PT Remala Abadi Tbk Berstandar ISO/IEC 29119 - Risa Salsabila; Alya Salsabilah; Chairul Anwar (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
The advancement of information technology in business encourages the use of web‑based systems to support digital marketing and content management activities. PT Remala Abadi Tbk, as an internet service provider, develops a Manage content system that provides product content request features, global visitor analytics, and real‑time SEO detection to support its marketing and sales teams. This study aims to evaluate the quality of the Manage content website using the ISO/IEC 29119 software testing standard through the Software Testing Life Cycle (STLC) approach. Functional testing is carried out using black‑box testing on core features such as staff authentication, content management, analytics dashboards, and user log activity, while non‑functional aspects are assessed through performance, usability, SEO, and compatibility testing. The results show that the main functions work as expected, although several minor bugs and performance issues are still found, indicating the need for further improvements to enhance system reliability and user experience.